Problem Analysis in Community Violence Assessment: revealing Early Childhood Trauma as a Driver of Youth and Gang Violence - Ross, Laurie Margot (International journal of offender therapy and comparative criminology, 2018)
Problem analysis conducted by a university-based research partner can provide communities with data-driven options to address the local drivers of serious youth and gang violence. Situated in Worcester, Massachusetts, this article describes how subsequent to early childhood trauma being identified as a potential driver of adolescent and young adult violence; problem analysis using local data confirmed that being the victim or witness of a traumatic incident before the age of 12 years was significantly correlated with involvement in violence in adolescence or young adulthood. Although there is a robust literature on the relationship between early childhood trauma and later delinquency, local decision makers did not consider this knowledge actionable until the research partner used the city’s own police records to demonstrate the extent of the problem in the city. Rigorous problem analysis, conducted collaboratively between practitioners and an academic research partner, helped to compel local change and ensured that strategies addressed the right risk factors and directed service to the appropriate target population.